Work Value, Tingkat Pendidikan Budaya Etnis Batak Toba Pada Anggota Satuan Brigade Mobile Kepolisian Daerah Sumatra Utara (Kajian Indigeneous) - Debi Angelina Br Barus; M. Rajab Lubis; Suryani Hardjo (Universitas Medan Area, 2019)
The purpose of this study to look at the work values Brimob from Toba Batak context and education. This study uses a mixed method approach indegeneous study Psychology. Methods correspond done with a snow ball and use open questionnaire as a means of data collection involved interviews to deepen the research. These results indicate that members of Brimob ethnic Batak Toba has a dominant work values are honor, wealth and family, this is in accordance with the philosophy of life’s Batak Toba that is Hagabeon, Hamoraon and Hasangapon. The 3H philosophy that mobilizes and motivates members to work discipline, responsibility, honesty, hard work and sincerity. In terms of education, found members who have S1 educated have the value of honorary work and responsibility, while members of high school educated have the value of discipline and honor work.